Effect of Rolling Process on Critical Temperature (Tc) in Ag/Bi1,6Pb0,4Sr2Ca2Cu3O10 Superconducting Wire with Addition of CNT Manufacture - Hilda Ayu Marlina; Agung Imaduddin; Kerista Sebayang; Pius Sebleku (PSI-Aceh, 2018)
Analisa pengaruh proses penarikan (rolling) terhadap suhu kritis (Tc) dalam pembuatan kawat superkonduktor Ag/Bi1,6Pb0,4Sr2Ca2Cu3O10 dengan penambahan CNT (carbonnanotube) telah dilakukakan. Kawat superkonduktor Ag/Bi1,6Pb0,4Sr2Ca2Cu3O10 dengan penambahan CNT merupakan kawat superkonduktor berbasis bismuth dengan penambahan CNT yang diselubungi Ag (Argentum), dalam penelitian ini Ag yang digunakan berdiameter awal 8 mm. Pembuatan kawat Ag/Bi1,6Pb0,4Sr2Ca2Cu3O10 dengan penambahan CNT tersebut dilakukan menggunakan metode PIT (Powder in Tube). Salah satu proses dalam metode PIT yang mempengaruhi suhu kritis (Tc) kawat Ag/Bi1,6Pb0,4Sr2Ca2Cu3O10 dengan penambahan CNT adalah proses penarikan (rolling). Dalam penelitian ini, Tc optimum didapatkan pada penarikan pertama dengan diameter kawat menjadi 5 mm dengan nilai Tconset 109,17 K dan nilai Tczero 71 K. Namun, pada penarikan kedua (penarikan berulang) hingga kawat berdiameter 2,6 mm diperoleh nilai Tconset sebesar 90 K, tetapi Tczero tidak dihasilkan. The analysis of rolling process to critical temperature (Tc) in the manufacture of Ag/Bi1,6Pb0,4Sr2Ca2Cu3O10 superconducting wire with additional CNT (carbonnanotube) has been done. The Ag/Bi1,6Pb0,4Sr2Ca2Cu3O10 superconducting wire with additional CNT is a superconducting wire based on bismuth by adding CNT shrouded by Ag (Argentum), in this study Ag used an initial diameter of 8 mm. This wire manufacture is done by using PIT (Powder in Tube) method. One of processes in the PIT method wich affect on Tc value is the process of withdrawal (rolling). In this study, the optimum Tc obtained at the first rolling with wire diameter to 5 mm with Tconset 109.17 K and Tczero 71 K. However, in the second rolling (rolling repeatedly) until the 2.6 mm diameter wire produced a value of Tconset of 90 K, but Tczero not produced. Keywords: Ag/Bi1,6Pb0,4Sr2Ca2Cu3O10, CNT, PIT method, RollingFERERENCESAbbas, M.M. et.al. 2015. “Superconducting Properties of Bi2-xSbxPb0,3Sr1,9Ba0,1Ca2Cu3O10+δ”. Journal of Applied Sciences Research. No. 22. Hal 164-172. Dadras, Y. Liu, Y.S. Chai, V. Daadmehr, K.H. Kim, Physica C 469 (2009) 55.De Bruyn Ouboter, R., Van Delft, D., Kes, P. H. 2012. “Discovery and Early History of Superconductivity”. In H. Rogalla, P. H. Kes (Eds.), 100 years of superconductivity (pp.1-29). Boca Raton, FL: CRC Press.Galvan, A. Durán, F.F. Castillón, E. Adem, R. Escudero, D. Ferrer, A. Torres, M. José-Yacamán, J. Supercond. Nov. Magn. 21 (2008) 271.Galvan, D.H., J.H.Kim., M.B. Maple, Hirata, G.A., dan E. Adem. 2000. Flux Pinning Effect of Embedded Carbon Nanotubes in Bi2Sr2CaCu2O8. Physica C, Vol : 341-348 : 1269-1270.Galvan, Shi Li, W.M. Yuhasz, J.H. Kim, M.B. Maple, E. Adem, Physica C 403 (2004) 145.Jabur, Akram R. 2012. “B2223 High Temperature Superconductor Wires in Silver Sheath, Filament Diameter Effect on Critical Temperature and Current Density”. Energy Procedia. 18. Hal 254-264.Joshua, dkk. 2016. Pembuatan Kawat Superkonduktor BSCCO-2223. Laporan Kerja Praktik.Lusiana. 2013. “Proses Pembuatan Material Superkonduktor BSCCO dengan Metoda Padatan”. Majalah Metalurgi. V 28.2.2013. Hal 73-82.Nurmalita. 2011. “The Effect of Pb Dopant On The Volume Fraction Of BSCCO-2212 Superconduntucting Crystal”. Jurnal Natural Vol. 11, No. 2.Rey, Christopher. 2015. “Superconductors in The Power Grid”. Woodhead Publishing. pp : 86.Z.Q. Yang, X.D. Su, G.W. Qiao, Y.C. Guo, S.X. Dou, F.R. de Boer, Physica C 325 (1999)